An ultrasensitive fluorescent aptasensor for detection of cancer marker proteins based on graphene oxide–ssDNA. Issue 72 (7th December 2018) - Wang, Chen-Feng; Wang, Zhen-Guang; Sun, Xin-Yue; Chen, Meng-Jiao; Lv, Yun-Kai
Abstract : A novel biosensing platform was developed by integrating a new ssDNA aptamer and graphene oxide (GO) for highly sensitive and selective detection of liver cancer biomarkers (AFP). Abstract : A novel biosensing platform was developed by integrating a new ssDNA aptamer and graphene oxide (GO) for highly sensitive and selective detection of liver cancer biomarkers (alpha-fetoprotein, AFP). The key concept of this biosensing platform is that the fluorescence of dye-modified ssDNA can be effectively quenched by GO after forming the hybrid structure of graphene oxide–ssDNA (GO–ssDNA). The AFP can selectively react with GO–ssDNA and lead to the decomposition of GO–ssDNA, which results in the recovery of fluorescence, and an increase in fluorescence intensity with the increasing concentration of AFP in the range of 0 to 300 pg mL −1 . The linear range was obtained from 1 to 150 pg mL −1 and the detection limit was 0.909 pg mL −1 . Moreover, this biosensing platform can be applied to serum and cell imaging for the detection of AFP. The results show that the proposed biosensor has great potential application in AFP-related clinical diagnosis and research.